Evaluasi Penerapan Media Biofilter Anaerob dan Mikroorganisme di Instalasi Pengolahan Air Limbah Domestik Industri Cat PT.X - Della Rahmah Dayanti; Rachmawati S. Dj (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Water pollution is a type of environmental pollution. Water pollution can be caused by wastewater containing pollutants that is discharged directly into water bodies or the environment. Domestic wastewater containing toxic substances can endanger the environment, human health, and the survival of other organisms. Therefore, domestic wastewater must first be treated before being discharged into water bodies. PT.X Paint Industry has a domestic wastewater treatment plant consisting of equalization, sedimentation and disinfection units. This study aims to identify an anaerobic biofilter treatment that is effective in reducing BOD and ammonia concentrations in domestic wastewater. Bioball media and Bacillus subtilis bacterial microorganisms were selected in this study as the proper components for use in anaerobic biofilter treatment in the PT. X paint industry. Bioball media has advantages such as a relatively large specific area and easy installation, while Bacillus subtilis microorganisms can reduce ammonia levels by 81.8% and BOD by 67.4%.